(untitled) (Revista Dialectus - Revista de Filosofia, 2023)
ENTREVISTA COM PROFESSORAS (ES) DE FILOSOFIA DO ENSINO SUPERIOR DO CEARÁ – BLOCO I Com: Ada Beatriz Gallicchio Kroef, Vicente Thiago Freire Brazil, Roberta Liana Damasceno Costa, Elizabeth Bezerra Furtado Por: Antônio Alex Pereira de Sousa, Paulo Willame Araújo de Lima